Rhizobial Exopolysaccharides and Type VI Secretion Systems: A Promising Way to Improve Nitrogen Acquisition by Legumes - De Sousa, Bruna Fernanda Silva; Castellane, Tereza Cristina Luque; Tighilt, Lilia; Lemos, Eliana Gertrudes de Macedo; Rey, Luis (Frontiers in Agronomy, 2021)
At the present there are numerous examples in which symbiotic nitrogen fixation by rhizobia can totally replace the use of nitrogen fertilizers for legume crops. Over the years, there has been a great effort by research institutions to develop and select rhizobial inoculants adapted to these crops. The symbiotic process is highly dependent on the dynamic exchange of signals and molecular nutrients between partners. Our focus in this review is to discuss two key determinants in successful symbiotic interactions of rhizobia able to nodulate pulses. One of them is the production of exopolysaccharides (EPS) and the other the presence of the type VI secretion system (T6SS). EPS are extracellular polymers weakly associated with the bacterial surface and are abundantly released into acid soils facilitating, among other functions, adaptation of rhizobia to this environment. By other hand, different protein secretion systems, involved in symbiosis, have been described in rhizobia. This is not the case of the T6SS. The current availability of various rhizobial genomes offers the possibility of discussing its role in the symbiosis. The study of these determinants will be of great utility for the selection of effective inoculants for legumes, a promising way to improve nitrogen acquisition by legumes.